Fetomaternal outcome in morbidly adherent placenta in a tertiary referral hospital - Paneerselvam, Amudha; Sundaram, Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Morbidly adherent placenta is often associated with major pregnancy complications requiring massive blood transfusions, peripartum hysterectomy, etc. The prior number of caesarean sections and placenta previa are the critical risk factors. The aim of this study is to evaluate the fetomaternal outcome in women with morbidly adherent placenta and to quantify the risk factors predisposing to it. Methods: This is a retrospective cohort study. The study population comprises women, who had C-section for placenta accreta, increta and percreta at Government Raja Mirasudhar Hospital, Thanjavur from May 2016 to September 2017. Results: Eighteen women out of 21,083 who delivered during the study period had morbidly adherent placenta with an incidence of 0.085%. The mean gestational age at the time of C-section was 32.4 weeks. Twelve (66.66%) out of eighteen women had prior one C-section, two (11.11%) women had prior 2 C-section and two (11.11%) women had prior 3 C-section.10 cases were diagnosed antenatally by radiological imaging. Seventeen out of eighteen women underwent caesarean hysterectomy (94.44%). Average blood loss was 1.8 litres. The mean intraoperative blood transfusions were 3 units of PRBC, 3 units of FFP and 1.4 units of platelet. There was no maternal mortality. The average total hospital stay was 20.46 days. 11 neonates were preterm (61%) and 5 neonates were term (27.74%). FGR was seen in 2 preterm neonates (12.5%). The NICU admission rate was 81% (n=13). The perinatal mortality rate was 31.25% (n=5). Conclusions: As most of the women ended up in caesarean hysterectomy, early diagnosis will enable appropriate planning for blood components, anaesthetic and surgical resources, thereby reducing adverse fetomaternal outcomes. This will also allow adequate preoperative counselling of the women involved.